Distinctive asymmetric bowl-like nanoparticles: Synthesis, properties and applications - Xin Fang; Yani Wang; Yuchao Lyu; Lishuang Ma; Xinmei Liu; Jianye Fu (Next Nanotechnology)
Bowl-like nanoparticles are highly promising for various applications in energy storage, catalysis, drug delivery, etc., owing to their unique asymmetric morphologies, packing behavior and corresponding optical, electrical, and magnetic properties. These bowl-like nanoparticles are also known as buckled, crumpled, red blood cell-like, and dimpled nanoparticles. Until now, plenty of synthesis strategies have been proposed including soft-templating method, hard-templating method, shrinkage of hollow nanospheres, etc. Bowl-like nanostructures with distinct compositions have been reported, e.g., polymer, carbon, silica-based, metal and metal oxides. Their half opening structure with a large pore cavity allows for efficient cargo loading, easy diffusivity for guest molecules, photothermal agent, batteries, microwave absorption and other properties. This review summarizes the widely used synthesis strategies, representative structures and applications of the bowl-like nanostructures. Moreover, we proposed the current challenges regarding on the synthesis strategies and prospects of future development. At last, this timely and comprehensive review may help foster the development of asymmetric bowl-like nanoparticles and expand the potential applications.